Investigation of Microholes Produced by Focused Ion Beam Micromachining - Mohd. Fuad, Nurul Hajar; Ali, Mohammad Yeakub (Department of Manufacturing and Materials,Kulliyyah of Engineering, IIUM, 2010)
This paper discusses the microfabrication of microholes using focused ion beam and investigation of geometrical integrity of microholes. Different combination of aperture size, probe current, acceleration voltage was applied for micromachining and optimized based on taper angle. Microholes with 3.0 μm of diameter were milled according to the optimized parameter using bitmap mode. The depth range of microholes was 1.0-5.5 μm. The hole‘s depth and taper angle were investigated for characterization. Each of the microholes was cross sectioned for investigation. A relationship of taper angle (θ), depth and aspect ratio were plotted. Low aspect ratio (less than 1) would give the lower taper angle and hence better integrity. Acceleration voltage of 25 kV, probe current of 41.5 pA and aperture size of 4 nm produced lower taper angle for different aspect ratio.